2014
DOI: 10.1017/jmo.2014.38
|View full text |Cite
|
Sign up to set email alerts
|

Contextualizing dirty work: The neglected role of cultural, historical, and demographic context

Abstract: Although perceptions of physically, socially, and morally stigmatized occupations – ‘dirty work’ – are socially constructed, very little attention has been paid to how the context shapes those constructions. We explore the impact of historical trends (when), macro and micro cultures (where), and demographic characteristics (who) on the social construction of dirty work. Historically, the rise of hygiene, along with economic and technological development, resulted in greater societal distancing from dirty work,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 77 publications
(106 reference statements)
0
31
0
Order By: Relevance
“…The centrally defining feature of many dirty work jobs is the interactions with those whom society has marginalized; for example, correctional officers must be around prisoners and bill collectors must contact debtors. Previous research has found that a typical defense mechanism for those in dirty work jobs is to blame these stigmatized clients for their problems and then distance themselves from them (Ashforth & Kreiner, ; Juhila, Hall, & Raitakari, ). We found, however, that dirty work managers attempted to foster not blaming or distancing but, rather, taking the perspective of clients, that is, empathizing with them.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The centrally defining feature of many dirty work jobs is the interactions with those whom society has marginalized; for example, correctional officers must be around prisoners and bill collectors must contact debtors. Previous research has found that a typical defense mechanism for those in dirty work jobs is to blame these stigmatized clients for their problems and then distance themselves from them (Ashforth & Kreiner, ; Juhila, Hall, & Raitakari, ). We found, however, that dirty work managers attempted to foster not blaming or distancing but, rather, taking the perspective of clients, that is, empathizing with them.…”
Section: Resultsmentioning
confidence: 99%
“…The centrally defining feature of many dirty work jobs is the interactions with those whom society has marginalized; for example, correctional officers must be around prisoners and bill collectors must contact debtors. Previous research has found that a typical defense mechanism for those in dirty work jobs is to blame these stigmatized clients for their problems and then distance themselves from them (Ashforth & Kreiner, 2014a;Juhila, Hall, & Raitakari, 2010 Other managers reported coaching newcomers to act in a manner that was contrary to occupational stereotypes so as to diffuse clients' antipathy. For example, Manager 1 of exterminators told us how he trains his workers in entomology so that they are very knowledgeable about potential bug problems and can counter the prevailing stigma of the job:…”
Section: Developing Perspective Takingmentioning
confidence: 99%
“…There is thus an “overlap” between forms of low status dirty work and categories of socio‐economic and/or demographic status. Here, Ashforth & Kreiner, : 430) refer to a “recursive loop” whereby “questionable essentialist stereotypes” take on a normative slant and where low‐prestige dirty work is devolved to marginalised demographic categories, reinforcing the relationship between the two.…”
Section: Gender Class and Race And “Embodied Suitability”mentioning
confidence: 99%
“…In the present context, it is unwanted jobs that are socioeconomically unhygienic. Against the liberal discursive background of individualism and choice, there is a fundamental association between “perceptions of dirty jobs and dirty people” (Ashforth and Kriener :432). These are chiefly the poor and the racialized who suffer from the perception that they somehow choose lesser jobs or simply do not work hard enough to advance.…”
Section: Bringing Dirt Online: Socioeconomic Hygiene and Dirty Workmentioning
confidence: 99%
“…More and more Canadians—including those with postsecondary qualifications—are finding themselves in (often multiple) part‐time, temporary, and precarious jobs to make ends meet (Fuller and Stecy‐Hildebrandt ; Lewchuk, Clarke, and de Wolff ). Most of these jobs are, put simply, extremely dirty—not only physically dirty, but also rife with moral and social “dirt.” Collectively, sociologists and psychologists have insisted that we must make sense of dirty work within wider racialized, gendered, and classed matrices that construct certain types of work and workers as immoral, demeaning, disgusting, or otherwise subordinating (Ashforth and Kreiner , ; Ashforth et al. ; Dick ).…”
mentioning
confidence: 99%